2011
DOI: 10.1002/pbc.22989
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic surveillance for asymptomatic late‐onset anthracycline cardiomyopathy in childhood cancer survivors

Abstract: BackgroundThe optimal frequency of echocardiographic surveillance in asymptomatic childhood cancer survivors exposed to anthracyclines has not been established. We evaluated the effectiveness of performing surveillance echocardiograms according to the Children's Oncology Group's (COG) Long‐Term Follow‐Up Guidelines for Survivors of Childhood, Adolescent, and Young Adult Cancers in survivors ≥1 year from concluding therapy.MethodsWe reviewed all children treated at our institution with anthracycline chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
2
26
0
2
Order By: Relevance
“…Our findings further illustrate this limitation of echocardiography as a screening modality, where only 72% of patients with abnormal echocardiography had reproducible results. This illustrates a limitation of some studies that have reported high rates of single‐episode echocardiographic abnormalities among survivors, as a significant proportion of exposed patients with an abnormal echocardiogram at a single visit may be misclassified as cases, potentially causing an overestimation of ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings further illustrate this limitation of echocardiography as a screening modality, where only 72% of patients with abnormal echocardiography had reproducible results. This illustrates a limitation of some studies that have reported high rates of single‐episode echocardiographic abnormalities among survivors, as a significant proportion of exposed patients with an abnormal echocardiogram at a single visit may be misclassified as cases, potentially causing an overestimation of ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most significant complications of pediatric cancer treatment is the occurrence of cardiac morbidity, occurring in up to 57% of survivors treated with anthracycline chemotherapy . The receipt of radiation therapy (RT) to the heart is also strongly associated with cardiac morbidity in these patients …”
Section: Introductionmentioning
confidence: 99%
“…XRT dose: ≤30 Gy 10.8%>30 Gy 23.2%Asymptomatic cardiac dysf. Graded per CTCAE LVSF as primary outcome (1 st echo) LVSF<30% XRT ≤30 vs. >30 Gy: 12.5% vs. 31% Multivariate regression (SF<30%): No Radiotherapy (Ref) Odds RatioThorax: 3.49 (1.6–7.6)Abdomen: 2.66 (1.0–7.05)Spine: 0.64 (0.23–1.74)TBI: 0.53 (0.10–2.87)Abosoudah 24 2011Prospective cohort -Survivorship clinic1995–20033.0 yrs (1–10)4-year survivors 896 anthracycline-treated603 eligible for study 469 >=1 screening echoAge at Dx: 7.7 (SD 4.6)Anthracycline: Mean – 205 (114.7)Chest XRT: 34%No dose in model Field involving heart Screening echo per COG LTFU Guidelines Not limited to abn EF/FS Multivariate regression: No radiation (Ref)RT to heart: HR 1.7 (1.1–2.8)Time to first abnormal echocardiogramScreening frequency driven by age, anthracycline dose, and XRT so unclear implicationHudson 25 2007Cross-sectional9.0 (3.0–18.0)223 anthracycline-treated Vs. 55 – not at riskAge at Dx: 5.5 (0–23.6)Anthracycline (AR) Med: 202 (25–510)Anth + XRT: 26.9%Chest XRT: 2.7%Screening echo.LVSF, Wall stress Univariate regression (SF<28%): No Cardiac RT (Ref)RT: OR 0.9 (0.4–2.05)AsymptomaticOne time-pointNo cardiac dose quantificationKremer 29 2002Review of Frequency and Risk Factors of anthracycline-induced sub clinical cardiotoxicityMedline: 1966–2001 >50 children/study58 articles reviewedLimitations in many: Missing info Non-rep. populationsNon-original research Validity evaluated in 25 studies 10 studies w/RF analyses6 studies which defined an abnormal SF with validity score>5 Risk Factor analysis: Steinherz (1991)Lipshutz (1991)Silber (1993)Sorensen (1995)Lipshultz (1995)Pihkala (1996)Sorensen (1997)Nysom (1998)Lanzarini (2000)Bossi (2001)1 Study with chest radiation dose as predictor (limited to FS or EF abn) Risk Factor analysis: Steinherz (1991), N=201 >cumulative anth dose × f/up >mediastinal radiationNo dose-effect calculationsNot all 10 studies had populations that would have received chest radiation (ie: ALL, AML) …”
Section: Appendixmentioning
confidence: 99%
“…[19][20][21][22][23][24] The current COG guidelines recommend routine echocardiograms or nuclear medicine-gated heart studies at a frequency of once a year to once every 5 years after completing therapy, depending on patient age, whether concurrent radiation was received, and the cumulative anthracycline dose. 25 Recommendations with regard to cardiac monitoring before and during chemotherapy were published by the Children's Cancer Study Group in 1992.…”
Section: Discussionmentioning
confidence: 99%
“…19 The COG and other consensus panels recommend routine postchemotherapy echocardiographic follow-up to screen for late cardiotoxicity in childhood cancer survivors. [20][21][22][23][24] The necessity and effectiveness of late cardiac screening is increasingly validated [20][21][22] ; however, the importance and cost-effectiveness of routine echocardiographic studies before and during treatment in asymptomatic children who are receiving anthracycline chemotherapy agents remain incompletely defined. To further define the role of routine echocardiograms in children before and during treatment with anthracycline drugs, we conducted a retrospective study of our experience to determine the impact of routine, early monitoring for cardiotoxicity and therapy modification.…”
Section: Introductionmentioning
confidence: 99%